2017
DOI: 10.3389/fpls.2017.00507
|View full text |Cite
|
Sign up to set email alerts
|

Pruning System and Foliar Application of MgSO4 Alter Yield and Secondary Metabolite Profile of Rosa damascena under Rainfed Acidic Conditions

Abstract: Damask rose (Rosa damascena Mill.) is one of the most high-value essential oil-bearing plants in the world. However, the flower yield and quality of essential oil of R. damascena are largely influenced by the pruning practices and balanced supply of plant nutrition. The objective of this study was to test the hypothesis whether the pruning system and foliar fertilization of MgSO4 would influence the flower yield, growth and secondary metabolites profile of R. damascena. A field experiment of 10 treatment combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
(53 reference statements)
5
18
0
Order By: Relevance
“…Numbers of flowers plant -1 and fresh flower weight plant -1 produced significantly (p ≤ 0.01) higher positive correlation with flower yield (0.99), essential oil content (0.77), while, showed positive correlation with numbers of branches plant -1 (0.44). Similar results were observed in correlation matrix of damask rose in which data revealed that flower yield was significantly and positively correlated with the number of flower [34]. Plant height (cm) had highly positive significant correlation for LAI (0.89), N-S plant spread (0.88) and E-W plant spread (0.82), however, had positive correlation for number of branches plant -1 .…”
Section: Resultssupporting
confidence: 78%
“…Numbers of flowers plant -1 and fresh flower weight plant -1 produced significantly (p ≤ 0.01) higher positive correlation with flower yield (0.99), essential oil content (0.77), while, showed positive correlation with numbers of branches plant -1 (0.44). Similar results were observed in correlation matrix of damask rose in which data revealed that flower yield was significantly and positively correlated with the number of flower [34]. Plant height (cm) had highly positive significant correlation for LAI (0.89), N-S plant spread (0.88) and E-W plant spread (0.82), however, had positive correlation for number of branches plant -1 .…”
Section: Resultssupporting
confidence: 78%
“…Akhtar et al (2016) proved that pruning is effective for increasing flowers yield. Our results are in harmony with the report of Pal & Mahajan (2017) who reported that the proper pruning system could increase the flowers yield by improving the levels of both photosynthetic pigment and N content. Phosphorous has a pivotal role in genetic inheritance, membrane structure, signaling pathways, and metabolism, and therefore it is considered essential for all plants (Ashley et al, 2011;Butusov & Jernelöv, 2013) which may explain the enhanced flower yield due to its application.…”
Section: Discussionsupporting
confidence: 92%
“…species, Rosa damascena Miller var. trigintipetala Dieck or Taif-rose is extensively cultivated for valuable volatile oil and its products such as rose concrete, absolute and rose water and the perfumes (Rusanov et al, 2005;Pal & Mahajan, 2017;Al-Yasi et al, 2020;Hassan et al, 2021). Further, the rose volatile oil is widely used in pharmaceutical, food and flavour & fragrance industries (Baydar & Baydar, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No statistical significance was noted at the harvesting stage except at E.V.S, L.V.S, and B.S (p < 0.05), as shown in Figure 2 B . It is expected that cutting would encourage branching, and additionally, the well-established plants in the second cut would have a robust root system that supports vegetative growth ( Chimonidou-Pavlidou, 2000 ; Pal and Mahajan, 2017 ).
Figure 2 The effect of Irrigation treatments on; A & B: Number of branches in cut 1&2; C & D: plant heights in cut 1&2 at different growth stages.
…”
Section: Resultsmentioning
confidence: 99%